BIOSORBEN KITOSAN CANGKANG KEONG SAWAH TERHADAP PENYERAPAN ZAT WARNA METHYLENE BLUE - iget rais; Nurhaeni; Ruslan; Dwi Juli Pusptasari (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2019)
Biosorbent studies on methylene blue absorption using chitosan from rice conch shell have been carried out. This research was carried out with variations in contact time of 1, 2, 3, 4, 5, and 6 hours with the aim to determine the contact time required to adsorb Methylene Blue dyes by chitosan from rice conch shell with the highest adsorption capacity. The results showed that the contact time required to adsorb Methylene Blue dye by a chitosan from rice conch shell was 6 hours with the highest adsorption capacity of 85.05%. Keywords: Chitosan, adsorption, Methylene Blue